2020
DOI: 10.1002/pld3.239
|View full text |Cite
|
Sign up to set email alerts
|

N6‐methyladenosine and RNA secondary structure affect transcript stability and protein abundance during systemic salt stress in Arabidopsis

Abstract: After transcription, a messenger RNA (mRNA) is further post‐transcriptionally regulated by several features including RNA secondary structure and covalent RNA modifications (specifically N 6 ‐methyladenosine, m 6 A). Both RNA secondary structure and m 6 A have been demonstrated to regulate mRNA stability and translation and have been independently linked to plant responses to soil salinity levels. However, the effect of m 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 64 publications
2
63
1
Order By: Relevance
“…Under external stress, the increase of m6A marks in the 5' untranslated region (UTR) promoted the translation of drought-resistant mRNA ( Meyer et al, 2015 ). Meanwhile, m6A RNA methylation can also alleviate the damage of abiotic stress via modulating mRNA abundance, splicing, stability, and decay ( Zhou et al, 2015 , 2018 ; Duan et al, 2017 ; Kramer et al, 2020 ). Additionally, recent studies have shown that the dynamic redistribution of m6A levels under stress leads to m6A marks mainly enriched in genes related to primary and secondary metabolisms ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under external stress, the increase of m6A marks in the 5' untranslated region (UTR) promoted the translation of drought-resistant mRNA ( Meyer et al, 2015 ). Meanwhile, m6A RNA methylation can also alleviate the damage of abiotic stress via modulating mRNA abundance, splicing, stability, and decay ( Zhou et al, 2015 , 2018 ; Duan et al, 2017 ; Kramer et al, 2020 ). Additionally, recent studies have shown that the dynamic redistribution of m6A levels under stress leads to m6A marks mainly enriched in genes related to primary and secondary metabolisms ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study in Arabidopsis found that RNA structures in both shoot and root were globally refolded in response to salt stress, leading to an inverse change of RNA abundance [41]. In contrast, protein interaction profile sequencing (PIP-seq), a method that simultaneously identifies protein-bound regions on a transcriptome-wide scale to examine global patterns of in vitro RNA secondary structure, reached the opposite conclusion following systemic salt stress in Arabidopsis [42]. They observed that N 6 -methyladenosine (m 6 A) RNA changes anti-correlated with alterations of RNA secondary structures in response to salt stress [42].…”
Section: The Role Of Rna Structure In Translationmentioning
confidence: 99%
“…They observed that N 6 -methyladenosine (m 6 A) RNA changes anti-correlated with alterations of RNA secondary structures in response to salt stress [42]. Interestingly, the salt-specific m6A deposition and the associated weak RNA secondary structure resulted in increases in mRNA stability [42]. These contrasting results might be due to the different time periods employed for salt treatment [41,42].…”
Section: The Role Of Rna Structure In Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidences demonstrated that m 6 A also participates in plant responses to various abiotic stresses. In Arabidopsis, changed m 6 A deposition affects RNA secondary structure under salt stress, resulting in increased stability of mRNA transcripts of abiotic stress response genes (Kramer et al, 2020). Additionally, ALKBH6 (eraser) mutation results in increased salt, drought, and heat stress sensitivity during seed germination (Huong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%